Intensitas dan Prevalensi Endoparasit pada Sistem Pencernaan Ikan Kerapu Cantang Ephinephelus fuscoguttatus x Ephinephelus lanceolatus di Tiga Lokasi Budidaya Tanjungpinang - Septa Nugraha; Aminatul Zahra; Shavika Miranti (Intek Akuakultur, 2022)
This study aims to identify the types of endoparasites found in the digestive organs including the oral cavity, throat, stomach, intestines, anus in cantang grouper. This research was conducted from April to May 2021 at the Laboratory of Fish Quarantine Station for Quality Control and Fishery Products Class II Tanjungpinang. The method used is observation and sampling is done by random sampling technique, the sample used is 30 individuals. The results of the research at Hsrt Mina Bina Sejahtera showed that 10 samples of fish were infected with endoparasitic worms in the mouth of the phylum Arthropoda, spisies Caligus sp. , Lepeophteirus salmonis, Lepeophtheirus sekii, Aphotopontius sp. with a total of 128 tails, while in the intestine and stomach there is 1 type of endoparasite that attacks from the phylum Platyhelminthes species Lecithochirium jaffense and phylum Nematoda species Capillaria philippininensis. Research in Maju Mandiri Endoparasite worms in the digestive system of cantang grouper were found in the mouth of the phylum Arthropoda, spisies Caligus sp, Lepeophteirus salmonis, a total of 34 individuals. Research at Rm Ramdhan Dompak Endoparasite worms in the digestive system of cantang grouper were found in the stomach of the Nematoda phylum Anisakis simplex species with a total of 54 individuals. While in the mouth there are 2 types of parasites of Caligus sp species, Lepeophteirus salmonis, with a total of 38